2004
DOI: 10.1021/jf0351873
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar and Year-to-Year Variation of Phytosterol Content in Rye (Secale cereale L.)

Abstract: Intake of phytosterols (and -stanols) has been shown to decrease the level of low-density lipoprotein cholesterol and thus protect against development of cardiovascular diseases. Therefore, studies on the cultivar and year-to-year variation in phytosterol content in rye grains have been performed. The phytosterol content and composition of different rye cultivars, grown under identical conditions on the same field in three consecutive years, were analyzed. Both cultivar and year-to-year variation in sterol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
5
18
0
3
Order By: Relevance
“…In order to maximize the content of phytosterols, squalene and tocopherols in plant foods, it is important to consider factors such as processing conditions, cultivar, growing season and planting location [25,[38][39][40][41][42][43]. In addition, enhanced contents of these bioactive components may be achieved through crop engineering [44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…In order to maximize the content of phytosterols, squalene and tocopherols in plant foods, it is important to consider factors such as processing conditions, cultivar, growing season and planting location [25,[38][39][40][41][42][43]. In addition, enhanced contents of these bioactive components may be achieved through crop engineering [44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…It seems, based on clinical experiments, that phytostanols are more efficient [24]. Phytosterols content in common cereal grains and their by-products have been extensively studied [6,10,23,[25][26][27][28][29]. Most of these reports studied sterol content on commercial samples, which considerably limits source traceability.…”
Section: Introductionmentioning
confidence: 99%
“…Among the compounds exanimated in the European HEALTHGRAIN project, phytosterols contents in common cereal grains took an important place. A large variability of sterols content was found in Triticum aestivum, T. spelta, T. turgidum var durum, T. turgidum var dicoccum, T. monococcum [11,[30][31][32], barley [33], Oat [25,34], rye [26,35]. Several reports have studied seed sterol content of a collection of durum and emmer wheats genotypes [11,[30][31][32]36].…”
Section: Introductionmentioning
confidence: 99%
“…Phytosterol content was significantly (t = 20.1, P \ 0.01) higher in November (2,824 mg kg -1 ) than in August (2,090 mg kg -1 ), whereas phytosterol composition was also markedly different in both environments. Seeds collected in November had less campesterol (6.5 % compared to 7.0 %, t = 2.3, P \ 0.05), stigmasterol (7.2 % compared to 10.6 %, t = 18.7, P \ 0.01), and D 7 -stigmastenol (2.4 % compared to 4.3 %, t = 4.6, P \ 0.01) and [18]. Conversely, studies in oil crops such as canola, soybean and sunflower reported that phytosterol content increases with higher temperatures [19][20][21].…”
Section: Resultsmentioning
confidence: 99%